Hands-on Dark Web analysis : learn what goes on in the Dark Web, and how to work with it - Retzkin, Sion (Packt Publishing, 2018)
Understanding the concept Dark Web and Dark Net to utilize it for effective cybersecurity Key Features Understand the concept of Dark Net and Deep Web Use Tor to extract data and maintain anonymity Develop a security framework using Deep web evidences Book Description The overall world wide web is divided into three main areas - the Surface Web, the Deep Web, and the Dark Web. The Deep Web and Dark Web are the two areas which are not accessible through standard search engines or browsers. It becomes extremely important for security professionals to have control over these areas to analyze the security of your organization. This book will initially introduce you to the concept of the Deep Web and the Dark Web and their significance in the security sector. Then we will deep dive into installing operating systems and Tor Browser for privacy, security and anonymity while accessing them. During the course of the book, we will also share some best practices which will be useful in using the tools for best effect. By the end of this book, you will have hands-on experience working with the Deep Web and the Dark Web for security analysis What you will learn Access the Deep Web and the Dark Web Learn to search and find information in the Dark Web Protect yourself while browsing the Dark Web Understand what the Deep Web and Dark Web are Learn what information you can gather, and how Who this book is for This book is targeted towards security professionals, security analyst, or any stakeholder interested in learning the concept of deep web and dark net. No prior knowledge on Deep Web and Dark Net is required